Minimal residual disease status determined by multiparametric flow cytometry pretransplantation predicts the outcome of patients with ALL receiving unmanipulated haploidentical allografts - Zhao, Xiao‐Su; Liu, Yan‐Rong; Xu, Lan‐Ping; Wang, Yu; Zhang, Xiao‐Hui; Chen, Huan; Chen, Yu‐Hong; Han, Wei; Sun, Yu‐Qian; Yan, Chen‐Hua; Mo, Xiao‐Dong; Wang, Ya‐Zhe; et al. (American journal of hematology, 2019)
This study evaluated the effects of pretransplantation minimal residual disease (pre‐MRD) on outcomes of patients with acute lymphoblastic leukemia (ALL) who underwent unmanipulated haploidentical stem cell transplantation (haplo‐SCT). A retrospective study including 543 patients with ALL was performed. MRD was determined using multiparametric flow cytometry. Both in the entire cohort of patients and in subgroup cases with T‐ALL or B‐ALL, patients with positive pre‐MRD had a higher incidence of relapse (CIR) than those with negative pre‐MRD in MSDT settings (P < 0.01 for all). Landmark analysis at 6 months showed that MRD positivity was significantly and independently associated with inferior rates of relapse (HR, 1.908; P = 0.007), leukemia‐free survival (LFS) (HR, 1.559; P = 0.038), and OS (HR, 1.545; P = 0.049). The levels of pre‐MRD according to a logarithmic scale were also associated with leukemia relapse, LFS, and OS, except that cases with MRD <0.01% experienced comparable CIR and LFS to those with negative pre‐MRD. A risk score for CIR was developed using the variables pre‐MRD, disease status, and immunophenotype of ALL. The CIR was 14%, 26%, and 59% for subjects with scores of 0, 1, and 2‐3, respectively (P < 0.001). Three‐year LFS was 75%, 64%, and 42%, respectively (P < 0.001). Multivariate analysis confirmed the association of the risk score with CIR and LFS. The results indicate that positive pre‐MRD, except for low level one (MRD < 0.01%), is associated with poor outcomes in patients with ALL who underwent unmanipulated haplo‐SCT.